Cardiac resident macrophages: key regulatory mediators in the aftermath of myocardial infarction - Chen, Cong; Wang, Jie; Liu, Chao; Hu, Jun (Frontiers in Immunology, 2023)
Acute myocardial infarction (MI) is a prevalent and highly fatal global disease. Despite significant reduction in mortality rates with standard treatment regimens, the risk of heart failure (HF) remains high, necessitating innovative approaches to protect cardiac function and prevent HF progression. Cardiac resident macrophages (cMacs) have emerged as key regulators of the pathophysiology following MI. cMacs are a heterogeneous population composed of subsets with different lineage origins and gene expression profiles. Several critical aspects of post-MI pathophysiology have been shown to be regulated by cMacs, including recruitment of peripheral immune cells, clearance and replacement of damaged myocardial cells. Furthermore, cMacs play a crucial role in regulating cardiac fibrosis, risk of arrhythmia, energy metabolism, as well as vascular and lymphatic remodeling. Given the multifaceted roles of cMacs in post-MI pathophysiology, targeting cMacs represents a promising therapeutic strategy. Finally, we discuss novel treatment strategies, including using nanocarriers to deliver drugs to cMacs or using cell therapies to introduce exogenous protective cMacs into the heart.